Progress in the knowledge of the genus Penthicus Faldermann, 1836 (Coleoptera: Tenebrionidae: Opatrini) of Iraq, Iran and Pakistan with descriptions of 17 new species - Nabozhenko, Maxim V.; Mofrad, Farhad Eshraghi (Zootaxa, 2025)
The darkling beetles of the genus Penthicus Faldermann, 1836 (Tenebrionidae: Blaptinae: Opatrini) from Iraq, Iran and Pakistan are revised. We used male and female genitalia for the first time for taxonomy of Penthicus. The subgenus Stonavus Reitter, 1904, subg. resurr. is resurrected from the synonymy with Penthicus and incudes three species-groups. Composition of all subgenera of Penthicus is given. Seven species don’t pass to any defined subgenus and require revision. The following new synonym is introduced: Penthicus iners (Ménétriés, 1832) = P. obesus (Kulzer, 1964), syn. nov. In total, one species of Penthicus is yet known from Iraq, 30 species from Iran and four species and one subspecies from Pakistan. The following 17 new species are described: in the nomynotypical subgenus: P. germanni sp. nov. (Iran) and P. mesopotamicus sp. nov. (Iran, Iraq); in Stonavus (all from Iran): P. achaemenus sp. nov., P. bam sp. nov., P. captiosus sp. nov., P. flatilatus sp. nov., P. farsistanus sp. nov. (Iran), P. grabantae sp. nov., P. iranensis sp. nov., P. kasatkini sp. nov., P. kermanicus sp. nov., P. khorasanicus sp. nov., P. pazukii sp. nov., P. shokhini sp. nov. (Iran), P. telnovi sp. nov., P. zarudnyi sp. nov.; in Myladion: P. pakistanicus sp. nov. (Pakistan). Penthicus turcomanicus (G.S. Medvedev, 1964) is recorded for Iran for the first time. Lectotypes are designated for Lobothorax oblongopunctatus Reitter, 1904, Lobodera freyi Schuster, 1937, Lobodera similis Schuster, 1937, Lobothorax horni Schuster, 1922, Lobothorax persicus Schuster, 1919, Heliophilus iners Ménétriés, 1832, Opatrum saginatum Ménétriés, 1832, Penthicus remotus Reitter, 1896 and Lobodera tzaidamica Bogatchev, 1951. A key to species from the studied territories is given.